ECTHR_CHAMBER 32563/04 vom 11. Dezember 2012 , AFFAIRE ILEANA CONSTANTINESCU c. ROUMANIE - Ecthr Chamber (2012)
Violation de l'article 10 - Liberté d'expression-Générale (Article 10-1 - Liberté d'expression); Violation: 10;10-1